WATER QUALITY INDEX OF WELL WATER SAMPLES OF BAJOGA AND ENVIRONS, FUNAKAYE LOCAL GOVERNMENT AREA, GOMBE STATE - BABA, A. M.; HARUNA, N.; MIJINYAWA, H.; ISAAC, E. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2021)
Safe drinking water is essential to humans; hence the quality of drinking water is of paramount importance. This study was aimed to evaluate the quality of drinking water from ten (10) different wells in Bajoga and environs in Funakaye Local Government Area (L.G.A) of Gombe state, Nigeria. The water samples were collected and analyzed for Water Quality Index (WQI). Ten physico-chemical parameters were used to calculate the WQI. These are pH, electrical conductivity, turbidity, chlorides, phosphate, calcium, magnesium, total hardness, total dissolved solids and total suspended solids. The results for the parameters analyzed showed 7.00-7.70 pH; 132.1-578μs/cm EC; 1.60-7.52NTU turbidity; 66.6-385ppm TDS; 0.77-95mg/L TSS; 254.95- 566.65mg/L Hardness; 151.9-379.85mg/L chloride; 103.00-291.50mg/L calcium; 28.45- 100.00mg/L magnesium and 0.50-6.45mg/L phosphate. The results of WQI obtained from different wells were found to fall between 27.60-95.80 which means some were good while some were very poor. It is therefore concluded that some of the water samples analyzed from the wells of Bajoga and Environs were suitable for drinking and for other domestic activities while most were not.